The Impact of Nutritional Supplementation During Pregnancy on the Incidence of Gestational Diabetes and Glycaemia Control - Ibrahim, Ibrahim; Bashir, Mohammed; Singh, Parul; Al Khodor, Souhaila; Abdullahi, Hala (Frontiers in Nutrition, 2022)
The nutritional state before and throughout pregnancy has a critical impact on the women's health and the baby's development and growth. The release of placental hormones during pregnancy induces/ increases maternal insulin resistance and promotes nutrition utilization by the foetus. Gestational Diabetes Mellitus (GDM) is the most common medical complication in pregnancy and is associated with significant maternal and fetal morbidity. Several studies have examined the effect of physical activity, healthy eating, and various food supplements on the risk of developing gestational diabetes (GDM) and related outcomes. Among those, Myo-Inositol supplementation has shown encouraging results in the prevention of GDM. Maternal vitamin D deficiency has been associated with an elevated risk of GDM, and supplementation can improve glucose haemostasis by lowering fasting blood glucose, HbA1c, and serum insulin concentration. Probiotics modulate the gut microbiota leading to an improved glucose and lipid metabolism, which is proposed to reduce the risk of GDM. We aim to review the strength and limitation of the current evidence for using some nutritional supplements either as single agents or in combinations on the risk of developing GDM and on glycaemic control.